2013
DOI: 10.1177/0897190013504954
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Assessment of a Pharmacist-Directed Seamless Care Program in an Ambulatory Oncology Clinic

Abstract: The primary goal of seamless care is improved patient outcomes and improved standards of care for patients with cancer. The pharmacy service of the Newfoundland Cancer Treatment and Research Foundation conducted a randomized control study that measured clinical and humanistic outcomes of a pharmacist-directed seamless care program in an ambulatory oncology clinic. This article focuses on the intervention group, particularly the identification of drug-related problems (DRPs) and utilization of health care servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 5 publications
1
64
1
1
Order By: Relevance
“… 58 Addition of face-to-face encounters has also been found to contribute to enhanced pharmacist–patient relationships 59 , 60 and provider satisfaction. 23 , 61 Documentation of care in the patient’s medical record is critical to communicate findings and interventions to the interprofessional team 58 , 61 , 62 ( Fig 1 ).…”
Section: Practice Managementmentioning
confidence: 99%
“… 58 Addition of face-to-face encounters has also been found to contribute to enhanced pharmacist–patient relationships 59 , 60 and provider satisfaction. 23 , 61 Documentation of care in the patient’s medical record is critical to communicate findings and interventions to the interprofessional team 58 , 61 , 62 ( Fig 1 ).…”
Section: Practice Managementmentioning
confidence: 99%
“…Pharmacists were involved in the care of three‐quarters of the patients making one or more intervention. To our knowledge, no study has been published previously that included both a hospital as well as an outpatient pharmacist in one palliative team, even though the need for seamless care between primary and secondary care settings in this patient population is well established . We showed that the specific fields of expertise of both types of pharmacists may work synergistically in this patient population.…”
Section: Discussionmentioning
confidence: 74%
“…Em estudo realizado por Hussainy et al na Austrália, a inclusão de farmacêuticos nas equipes aumentou o conhecimento relacionado a medicamentos por parte da equipe de CP e dos pacientes, melhorando o manejo das prescrições e reduzindo erros relacionados 16 . Quando o paciente faz a escolha de receber CP no ambiente domiciliar, o reconhecimento da forma como essa terapia será manejada faz com que a alta hospitalar tenha êxito ou não 17 . A realização de estudos na área de CP que avaliem a eficácia e segurança de medicamentos pode garantir uma melhor qualidade de atendimento, qualificando a unidade hospitalar ou o cuidado domiciliar.…”
Section: Discussionunclassified